Sentidos de psicoterapia para homens gays - Pereira, Guilherme Bessa Ferreira (2014)
Psychotherapy works with sexuality issues since its beginning. Initially, the descriptions of homosexualities presenting them as sexual deviance or disease. Such understanding oriented psychotherapies to develop working methods that led to the “cure” of gays and lesbians. The critique of this conception and the LGBT social movements led to the homosexuality depathologization. However, this is not enough to ensure that psychotherapies won’t reproduce oppression to the homosexuality. In this sense, it’s necessary to think about how psychotherapy approach the homosexual people care. The scenario of these reflections is the field of this study. This work aimed to reflect on the psychotherapy meanings produced by gay men who had a psychotherapy care. The study gathered 10 gay men living in Uberlândia- MG. The narratives were accessed through a semi-structured interview. The data was transcribed and examined using analytic discourse. Through the analysis were identified some meanings: Not all interviewers sought psychotherapy to deal with homosexuality issues; but when they did, it was “masked” in others issues; The meanings of “help” were presented as interventions that helped deal with the process of "accept" and "come out" the homosexuality, as well as, manage with family conflicts; Who declared that psychotherapy didn’t help also said that their care professionals repressed their gay identity somehow. The study therefore provides insights about the role psychotherapists offers care for people who deal with homosexuality issues. Other studies, that reflect about the heteronormativity discourses in the construction of psychotherapeutic experience, are required.